Способ повышения износостойкости поверхности изделий из керамики на основе диоксида циркония - Гынгазов С. А. Сергей Анатольевич; Суржиков А. П. Анатолий Петрович; Франгульян Т. С. Тамара Семёновна; Мельников А. Г. Александр Григорьевич; Коваль Н. Н. Николай Николаевич; Девятков В. Н. Владимир Николаевич; Григорьев С. В. Сергей Владимирович
опубл. 20.11.06